Dismissal of Nizar as Chief Minister in Perak: the constitutional issues / Abdul Hakim Ab Keram@ Ab Karem … [et al.] - Ab Keram@ Ab Karem, Abdul Hakim; Rorote, Daryl Clarence; Abdul Rahman Shah, Mohd Ardi Shah; Yahya, Abdul Hafiz (2011)
The objective of the study is to identify and discuss the legal issues in constitutional law in terms of rights and limitations of the Sultan in dismissing the Menteri Besar if the situation arises that is loss of majority confidence in the state legislative assembly. On this issue, there is already some review made by other writers in India and it has provided the foresight for the Perak situation. The issues had arisen in Malaysian politics first in Sabah and it had produced diverse outcome by different judgment. Thus it shows the need for a review in term of constitutional context. Both the qualitative and quantitative method was used in this research. The information and materials that had been gathered were obtained from statutes, books, articles and periodical journals that related to constitutional issue of situations when the leader had lost the confidence of the House. Reference include of local and foreign sources. The scope of the study only limited to the power of Ruler or Sultan to the act of dismissing the Menteri Besar if have lack of majority confidence in state assembly. This research will provide an insight to the public to view the constitution as a whole and educate reader to the proper perspective of law. It also will enable future research in constitutional law to have additional sources and increase of knowledge in term of the power of the Sultan to dismiss the Menteri Besar when similar scenarios occur in future.